Perancangan Ulang Walker untuk Anak Diplegic Cerebral Palsy menggnakan Metode TRIZ - Putu Yoga Kurniawan Laksana; R. Hari Setyanto; Lobes Herdiman (Universitas Serang Raya, 2021)
Children with cerebral palsy at rehabilitation centers had difficulty performing walking rehabilitation with the existing walker. The resulted in children with cerebral palsy feeling dissatisfied with existing walkers, and this dissatisfaction resulted in their interest in ongoing rehabilitation. The existing walker does not accommodate the needs of cerebral palsy children, resulting in lousy form and dissatisfaction when using a walker for rehabilitation and reduce their interest in rehabilitation. Therefore it is necessary to redesign the walker to prevent bad form and increase the satisfaction level of children with cerebral palsy. The QUEST 2.0 questionnaire was used as a reference for designing. Based on the dimensions from the QUEST 2.0 questionnaire, the walker design criteria were determined. Then use the TRIZ method to resolve any technical contradictions that occur at the design stage. Assistive device